Problematika Prinsip Net Neutrality Berkenaan Layanan Jasa Netfix Pada Regulasi Nasional Indonesia - Dolok Yosuadi (MORALITY: Jurnal Ilmu Hukum, 2021)
This study Examined the need for strict implementation of regulations, especially on Netflix's as Over The Top (OTT) service, as an Information Technology service run by telecommunication service actors with content in the form of data, information or multimedia that runs through the internet network, services delivered are through the network. , the operator's infrastructure, but without any cooperation with operators or the government in Indonesia. The presence of Netflix in Indonesia can be likened to a merchant who sells at home without asking the owner's permission, and that is an example of bussiness unethical action. Netflix does not respect the sovereignty of the state by not taking care of permits, and there is no protection for the user community. Regulations related to OTT services such as Netflix have not been explicitly regulated in the existing laws in Indonesia, only broadly regulated in regulations on Telecommunications. The research was conducted using a normative juridical methodology with a qualitative approach. The results showed that there was a legal vacuum in Indonesian regulations regarding Net Neutrality which caused problems with OTT services such as Netflix. The conclusion in this regard, the government should immediately issue regulations related to OTT services such as Netflix to ensure legal certainty and justice for parties in carrying out business, especially in the field of telecommunications, in accordance with Indonesia's commitments in the international world and Indonesian citizen’s right. Keywords: Net Neutrality, Netflix, Broadcasting, Regulation